I have an equation that is a = d/b + d/c . Supposedly this means that

d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?

Someone told me to factor out d first but I'm not sure how. Thanks.

I have an equation that is a = d/b + d/c . Supposedly this means that

d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?

Someone told me to factor out d first but I'm not sure how. Thanks.

d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?

Someone told me to factor out d first but I'm not sure how. Thanks.

- stapel_eliz
**Posts:**1743**Joined:**Mon Dec 08, 2008 4:22 pm-
**Contact:**

gcmky wrote:I have an equation that is a = d/b + d/c . Supposedly this means that

d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?

Someone told me to factor out d first but I'm not sure how. Thanks.

If you had "db + dc", would you be able to

stapel_eliz wrote:gcmky wrote:I have an equation that is a = d/b + d/c . Supposedly this means that

d = a / (1/b + 1/c) is also true. How do you get from the first equation to the second?

Someone told me to factor out d first but I'm not sure how. Thanks.

If you had "db + dc", would you be able tofactor?

Think I got it. Thanks.

a = d/b + d/c

a = d(1/b) + d(1/c)

a = d(1/b + 1/c)

a/(1/b + 1/c) = d(1/b + 1/c) / (1/b + 1/c)

a/(1/b + 1/c) = d

- stapel_eliz
**Posts:**1743**Joined:**Mon Dec 08, 2008 4:22 pm-
**Contact:**